Meningkatkan Keunggulan Kompetitif Melalui Knowledge Management - Restu Khaliq (UIN Antasari Banjarmasin, 2017)
Fakultas Dakwah dan Komunikasi IAIN AntasariBusiness competition is increasingly tight, not only to survive but the company should be able to have a competitive advantage. Companies need to know how to take advantage of the knowledge of the company to be able to increase their competitive advantage in the marketplace. Today many experts in management and organization theory raised the concept of knowledge management as a competitive advantage. Knowledge Management is a branch of science that presents an integrated approach to identify, capture, evaluate, retrieve and share all of an enterprise's information assets. Through this approach the company seeks to take advantage of his knowledge to build a strategy to build the foundation of the company's ability to compete.Keywords: competitive advantage, knowledge management